ETV6‐NTRK3 is a common chromosomal rearrangement in radiation‐associated thyroid cancer. Issue 6 (10th December 2013) - Leeman‐Neill, Rebecca J.; Kelly, Lindsey M.; Liu, Pengyuan; Brenner, Alina V.; Little, Mark P.; Bogdanova, Tetiana I.; Evdokimova, Viktoria N.; Hatch, Maureen; Zurnadzy, Liudmyla Y.; Nikiforova, Marina N.; Yue, Ning J.; Zhang, Miao; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND In their previous analysis of papillary thyroid carcinomas (PTCs) from an Ukrainian‐American cohort that was exposed to iodine‐131 (131I) from the Chernobyl accident, the authors identified RET/PTC rearrangements and other driver mutations in 60% of tumors. METHODS In this study, the remaining mutation‐negative tumors from that cohort were analyzed using RNA sequencing (RNA‐Seq) and reverse transcriptase‐polymerase chain reaction to identify novel chromosomal rearrangements and to characterize their relation with radiation dose. RESULTS The ETS variant gene 6 (ETV6)‐neurotrophin receptor 3 (NTRK3) rearrangement (ETV6‐NTRK3) was identified by RNA‐Seq in a tumor from a patient who received a high 131I dose. Overall, the rearrangement was detected in 9 of 62 (14.5%) post‐Chernobyl PTCs and in 3 of 151 (2%) sporadic PTCs (P = .019). The most common fusion type was between exon 4 of ETV6 and exon 14 of NTRK3. The prevalence of ETV6‐NTRK3 rearrangement in post‐Chernobyl PTCs was associated with increasing 131I dose, albeit at borderline significance (P = .126). The group of rearrangement‐positive PTCs (ETV6‐NTRK3, RET/PTC, PAX8‐PPARγ) was associated with significantly higher dose response compared with the group of PTCs with point mutations (BRAF, RAS; P < .001). In vitro exposure of human thyroid cells to 1 gray of 131I and γ‐radiation resulted in the formation of ETV6‐NTRK3 rearrangement at a rate of 7.9 × 10−6 cells and 3.0 × 10−6 cells, respectively. CONCLUSIONS The authors report the occurrence of ETV6‐NTRK3 rearrangements in thyroid cancer and demonstrate that this rearrangement is significantly more common in tumors associated with exposure to 131I and has a borderline significant dose response. Moreover, ETV6‐NTRK3 rearrangement can be directly induced in thyroid cells by ionizing radiation in vitro and, thus, may represent a novel mechanism of radiation‐induced carcinogenesis. Cancer 2014;120:799–807. © 2013 American Cancer Society.